Evolving Interplay Between Dietary Polyphenols and Gut Microbiota—An Emerging Importance in Healthcare - Ray, Suman Kumar; Mukherjee, Sukhes (Frontiers in Nutrition, 2021)
Polyphenols are natural plant compounds and are the most abundant antioxidants in the human diet. As the gastrointestinal tract is the primary organ provided to diet sections, the diet may be regarded as one of the essential factors in the functionality, integrity, and composition of intestinal microbiota. In the gastrointestinal tract, many polyphenols remain unabsorbed and may accumulate in the large intestine, where the intestinal microbiota are most widely metabolized. When assuming primary roles for promoting host well-being, this intestinal health environment is presented to the effect of external influences, including dietary patterns. A few different methodologies have been developed to increase solvency and transport across the gastrointestinal tract and move it to targeted intestinal regions to resolve dietary polyphenols at the low bioavailability. Polyphenols form a fascinating community among the different nutritional substances, as some of them have been found to have critical biological activities that include antioxidant, antimicrobial, or anticarcinogenic activities. Besides, it affects metabolism and immunity of the intestines and has anti-inflammatory properties. The well-being status of subjects can also benefit from the development of bioactive polyphenol-determined metabolites, although the mechanisms have not been identified. Even though the incredible variety of health-advancing activities of dietary polyphenols has been widely studied, their effect on intestinal biology adaptation, and two-way relationship between polyphenols and microbiota is still poorly understood. We focused on results of polyphenols in diet with biological activities, gut ecology, and the influence of their proportional links on human well-being and disease in this study.